Perancangan Perpustakaan Daerah di Bumi Serpong Damai dengan Konsep Green Architecture - Hardina Aryani; Dody Kurniawan; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
The library is one of the facilities for accessing information for the community as a supporter of the progress of education in Indonesia, at the village, sub-district, city / district, provincial and state levels. Of all regencies / cities throughout Indonesia, almost 90% have established public libraries. Bumi Serpong Damai is a planned city in Indonesia which is located in the sub-district of Serpong, South Tangerang. The city was inaugurated on January 16, 1984. BSD is one of the satellite cities of Jakarta which was initially designated as an independent city where all facilities are provided in the city including industrial, educational, tourist and residential areas. In BSD itself, the Al-Azhar BSD school, St.Ursula BSD school, Prasetya Mulya Business School, Indonesian Institute of Technology, International University Liasion Indonesia, Atma Jaya and others, unfortunately do not have their own library supporting facilities. BSD area. This library is designed by applying the concept of green architecture to minimize adverse impacts on the natural and human environment and produce a better and healthier place to live, which is done by utilizing energy sources and natural resources efficiently and optimally.